Análisis Fisicoquímico de Paracetamol 120 mg/5 mL solución oral de un Laboratorio Farmacéutico Nacional, Lima 2016 - Vargas Diaz, Leidy Sonia (2019)
This report of pre-professional practices describes the tests performed on the pharmaceutical product of paracetamol 120 mg/5 mL oral solution, with the aim of verifying its physicochemical quality according to the specifications established by the United States of America Pharmacopoeia USP 39. The following physicochemical tests were applied: physical characteristics, pH, delivery volume and identification by thin layer chromatography (TLC), where the physicochemical quality was determined according to the international standards that were made in the physicochemical area of the control laboratory quality. The results obtained were consistent for each test analyzed, so it was concluded that the product meets the specifications according to the USP 39 pharmacopoeia